Evaluación de la eficiencia de una celda de electrocoagulación a escala laboratorio para el tratamiento de agua - Aguilar Ascón, Edwar (2015)
The pollution caused by the use of water in many activities of human beings, has taken us to the need of using new technologies to the removal of contaminants from wastewater, one of them is the electrocoagulation. In this research we suggest the construction of an electrocoagulation reactor to evaluate the efficiency in the removal of COD (Chemical Oxygen Demand) from wastewater coming from the painting industry; it also wants to determine the best conditions of pH, conductivity, electric intensity and time of treatment. Based on the results we’ve gotten in the treatment of effluent with electrocoagulation, we determined an average efficiency in the 87 % of COD removal. This optimum ranges were gotten with an electrical intensity of I = 5 amperes, with the natural pH of the effluent in 7,12 and a 15 minutes treatment time, with which we accomplish the environmental compliance of the country. Other important aspect we ´ve seen in this research was the quality of the sludge produced in the treatment, with much more compact appearance than a physicochemical or biological sludge.